(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Plant fungus destroys vast swaths of agriculture. Fungus has been connected to a number of plant-based illnesses, posing considerable economic challenges. Plant fungus seeks to get beyond the plant’s immune system by activating PAMP-triggered immunity (PTI) and effector triggered immunity (ETI) defense. Successful infections, on the other hand, may override plant PTI and ETI, using pathogenic genes to defeat the host plant’s R-resistance genes, resulting in severe plant diseases. Fungus spores tend to land on plant surfaces in order to germinate, which requires perfect conditions such as moisture, nutrients, and a suitable host. If the conditions aren’t right, it may still exist even if it’s dormant. Chemical fungicides have been used for many years, however there have recently been indications that they are ineffective against emerging fungal strains. Furthermore, chemical fungicides are not biodegradable, posing a threat to the environment. This review attempted to offer a concise overview of plants that have anti-plant fungal properties. Because plant extracts include a variety of possible anti fungal agents with various modes of action, the pesticide industry may be able to produce plant-based fungicides on a large scale.